2006
DOI: 10.1074/jbc.m511154200
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell and Neutrophil Peptidases Attack an Inactivation Segment in Hepatocyte Growth Factor to Generate NK4-like Antagonists

Abstract: Hepatocyte growth factor (HGF) is a plasminogen-like protein with an α chain linked to a trypsinlike β chain without peptidase activity. The interaction of HGF with c-met, a receptor tyrosine kinase expressed by many cells, is important in cell growth, migration, and formation of endothelial and epithelial tubes. Stimulation of c-met requires two-chain, disulfide-linked HGF. Portions of an α chain containing an N-terminal segment and four kringle domains (NK4) antagonize HGF activity. Until now, no physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
1
32
1
Order By: Relevance
“…This apparent contradiction may be explained by, for example, the cellular location of the receptor; initial intracellular cmet may be transported to the plasma membrane at the onset of EAE where it would then be available for activation by HGF. Alternatively, natural occurring c-met antagonist such as NK1 and 2 and NK4-like protein (Chan et al 1991;Raymond et al 2006), both splice variants of full length HGF, may inhibit c-met activation in the CNS under systemic conditions. CNS injury may down regulate the levels of these antagonists, allowing c-met activation without a preceding increase in HGF.…”
Section: Hgf and C-met Expression In Eaementioning
confidence: 99%
“…This apparent contradiction may be explained by, for example, the cellular location of the receptor; initial intracellular cmet may be transported to the plasma membrane at the onset of EAE where it would then be available for activation by HGF. Alternatively, natural occurring c-met antagonist such as NK1 and 2 and NK4-like protein (Chan et al 1991;Raymond et al 2006), both splice variants of full length HGF, may inhibit c-met activation in the CNS under systemic conditions. CNS injury may down regulate the levels of these antagonists, allowing c-met activation without a preceding increase in HGF.…”
Section: Hgf and C-met Expression In Eaementioning
confidence: 99%
“…The α-chain of HGF also binds to the Met sema domain independently of the β-chain (10). Cleavage of HGF before cysteine 487 occurs with mast cell chymase, plasma kallikrein, or neutrophil elastase, each of which generates a free α-chain that can function as a competitive inhibitor of HGF (2,11). A synthetic version of the HGF α-chain containing the N-terminal domain and four kringle domains (NK4) has been explored as a HGF antagonist for anticancer therapy (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Under inflammation, HGF is digested by leukocyte-derived proteases, such as elastase, leading to generations of NK4 and HGF-␤ (i.e. HGF-daughter molecules) (13,17). We identified perlecan as a new receptor of NK4: the NK4⅐perlecan complex inhibits assembly of fibronectin, a key integrin ligand for supporting endothelial cell growth, resulting in the arrest of tumor angiogenesis (16).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that NK4 interacts with perlecan, resulting in the inhibition of surface fibronectin assembly and integrin-dependent endothelial growth (16). In addition to pancreatic elastase (11,13), leukocyte proteases and skin kallikrein also cleave HGF and generates an NK4-like fragment (17,18). In contrast to the unique functions of NK4, it is still unknown whether another HGF fragment, HGF-␤, has a biological function(s).…”
mentioning
confidence: 98%
See 1 more Smart Citation